Study on the Friction and Wear Performance of Lightly Loaded Reciprocating Carbon/Aramid-Based Composites - Yangyang Zhao; Guoyuan Zhang; Maotan Liang; Qunfeng Zeng (Advances in Materials Science and Engineering)
The preparation methods of T300 carbon cloth- and aramid cloth-reinforced epoxy resin and cyanate ester were proposed, and four kinds of composite samples were obtained. The friction coefficient and wear rate under different test times and loads were obtained using a reciprocating pin-disk tribology tester. The tribology pairs included pins or sliding blocks made from different metals (45 steel and brass) and the disk samples of the composites. The test results showed that the friction coefficients of the T300 carbon cloth- (T300/4211 and T300/BS-4) and aramid cloth- (aramid/4211 and aramid/BS-4) reinforced epoxy resin or cyanate ester changed from 0.09 to 0.3 and were low under dry friction conditions. Under 75 N, aramid/BS-4 coupled with 45 steel pins was the lowest friction coefficient, which was 0.09. In particular, the friction coefficient and wear rate of the composite-reinforced cyanate ester were the lowest, which meant that this composite may be more suitable for use under lightly loaded and reciprocating running conditions in space engineering. By comparing the surface morphologies of composites before and after the test, the wear mechanism of the composites was discussed and the lower friction coefficient and wear rate may originate from the abrasive wear effects occurring between the tribology pairs. The research results have important engineering significance for guiding the use of composites in the deployable mechanisms used in space engineering.